Analisa Dan Perancangan Sistem Manajemen Arisan Berbasis Android - Irawan Budiarto (JUSIBI (Jurnal Sistem Informasi dan E-Bisnis), 2019)
Abstract — Arisan is an activity of some people who collet money regularly with the same nominal, then draws between members to determine who the winner is. Where is arisan activities are carried out manually, namely by writing the names of members in a paper, put in a straw, then placed in a container, then drawn to determine the winner. Therefore, to provide convenience in conducting arisan activities which have been carried out manually, information technology is implemented by building a social gathering management system. At the beginning of this study a process of analysis and design of the social gathering management system will be carried out by approaching through PIECES needs analysis (Performance, Information, Economics, Control, Efficiency, Service) in finding the subject matter. The results of this study are a mock up or design of an arisan management system according to needs and based on the application of the methods used. From the results of this analysis and design it can then become a reference for making applications or developing social management Keywords—arisan, management, draw